ChemInform Abstract: Dendronephthols A—C, New Sesquiterpenoids from the Red Sea Soft Coral Dendronephthya sp. Issue 40 (30th September 2014) - Elkhayat, Ehab S.; Ibrahim, Sabrin R. M.; Fouad, Mostafa A.; Mohamed, Gamal A.
Abstract Dendronephthol A (I), B (II) and C (III) are evaluated toward their cytotoxic activity.